Work-related variables associated with perceptions of recovery-oriented care among Quebec mental health professionals. Issue 6 (November 2018) - Fleury, Marie-Josée; Sabetti, Judith; Grenier, Guy; Bamvita, Jean-Marie; Vallée, Catherine; Cao, Zhirong
Abstract : Background: Provider working conditions are important in mental health service delivery. Aims: To identify variables associated with perceived recovery-oriented care among mental health professionals. Method: A total of 315 mental health professionals and 41 managers across four Quebec service networks completed questionnaires. Univariate and multilevel mixed-effects linear regressions for bivariate and multivariate analyses were performed using independent variables from the input–mediator–output–input model and recovery-oriented care. Results: Recovery-oriented care related to: working in primary care or out-patient mental health services, team support, team interdependence, prevalence of individuals with suicide ideation, knowledge-sharing, team reflexivity, trust, vision (a subset of team climate), belief in multidisciplinary collaboration and frequency of interaction with other organisations. Conclusions: Optimising team processes (for example knowledge-sharing) and emergent states (for example trust) may enhance recovery-oriented care. Adequate financial and other resources, stable team composition, training on recovery best practices and use of standardised assessment tools should be promoted, while strengthening primary care and interactions with other organisations. Declaration of interest: None.